Impact of the timing of coronary revascularization relative to the transcatheter aortic valve implantation procedure: insights from a propensity score analysis based on a nationwide analysis. (25th November 2020) - Lantelme, P; Bisson, A; Lacour, T; Herbert, J; Ivanes, F; Bourguignon, T; Quilliet, L; Angoulvant, D; Harbaoui, B; Bonnet, M; Bernard, A; Babuty, D; et al.
Abstract: Background: The significance and the management of coronary artery disease (CAD) are disputed in patients treated by transcatheter aortic valve implantation (TAVI). In the presence of a significant CAD eligible for percutaneous coronary intervention (PCI), the issue of the timing of PCI relative to TAVI is unsettled. To answer this question, the present study aimed at comparing the short-term and long-term outcome in patients treated by staged PCI within a 90-day time interval before or after TAVI. Methods: Based on the French administrative hospital-discharge database, the study collected information for all consecutive patients treated with TAVI between 2014 and 2018. Patients treated with PCI in the preceding 90 days before the TAVI procedure (pre-TAVI PCI) or subsequent 90 days after the TAVI procedure (post-TAVI PCI) were included. All-cause mortality, cardiovascular mortality, stroke, myocardial infarction and a combined cardiovascular endpoint were assessed at 30 days after the last procedure (short-term) and during the whole follow-up (long-term). Propensity score matching was used for the analysis of outcomes. Results: 8613 patients met the inclusion criteria with a vast majority of pre-TAVI PCI patients (N=8324) as opposed to post-TAVI PCI (N=229). After propensity score matching, 2 groups of 227 patients with comparable characteristics were obtained. At 30 days, no significant difference was observed for any of the outcome tested with the exception of myocardial infarction more frequent in post-TAVI PCI (OR 2.43 [1.17–5.07]). After a mean [SD] follow-up of 459 [569] days, all outcomes were identical between subgroups. The figure below illustrates the Kaplan Meier curve for all-cause mortality. Conclusions: Our study based on a French nationwide database shows that PCI is performed pre-TAVI in a majority of cases, with no significant impact on outcome. Deferring PCI after TAVI seems safe and may provide an opportunity to make the decision on more objective parameters while the stenosis has been removed (such as FFR or IFR). In any case, the timing of PCI relative to TAVI does not seem to represent a concern and should be decided on an individual basis. Funding Acknowledgement: Type of funding source: None